Geochemical evidence for volcanic signatures in sediments of the Younger Dryas event. (1st November 2021) - Sun, Nan; Brandon, Alan D.; Forman, Steven L.; Waters, Michael R.
Highlights: Absence of Os isotope and highly siderophile element evidence of extraterrestrial input for the Younger Dryas sediments. Unradiogenic Os isotope ratios and highly siderophile element concentrations fingerprint volcanic aerosols. Correlated unradiogenic Os peaks supports the proposed distant and episodic volcanic mechanisms for the Younger Dryas event. Abstract: One of the prevailing hypotheses for the origin of the Younger Dryas (YD) cooling event is that it resulted from a bolide impact or airburst. Purported impact markers peak at or near the YD basal boundary layer at Northern Hemisphere locations. In this study, the 187 Os/ 188 Os ratios and highly siderophile element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances in a well-dated sediment section through the Younger Dryas at the Debra L. Friedkin site, Texas are reported. Unradiogenic 187 Os/ 188 Os peaks, which could be mantle-derived or extraterrestrial, have been found above, within, and below the YD basal boundary layer. Mass balance mixing models using chondrites or iron meteorites with upper continental crust fail to duplicate the chondrite-normalized HSE patterns of the sediment samples. These HSE signatures in the Friedkin site section replicate those found in Hall's Cave, Texas. The new results here thus independently confirm that the HSE abundances in the unradiogenic Os layers are likely a fingerprint of volcanic gas aerosols derived from large Plinian eruptions and not extra-terrestrial materials. To better constrain the lithological origins of YD sediments from the Friedkin and Hall's Cave sites, Texas, trace elements are presented here. The rare earth elements (REE) patterns and Ir, Ni, Ti and Zr abundances are also characterized with terrestrial signatures as opposed to impact melt rocks. An age profile correlation between the two study sites, further shows that three unradiogenic Os peaks overlap in time. The results are inconsistent with the extraterrestrial hypothesis and support instead an episodic and volcanic origin for the observed geochemical anomalies at the Debra L. Friedkin and Hall's Cave sites, Texas.